2017
DOI: 10.1016/j.ijrobp.2017.06.701
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Drives Prognosis in Women with Metastatic Breast Cancer

Abstract: stenosis. Of the 3 patients with significant CAD, distribution of CAD included the left anterior descending (LAD) artery (nZ3), right coronary artery (nZ1), and left circumflex artery (nZ1). Two patients had isolated LAD abnormalities. No significant difference in mean MHD was found between patients with or without CAD on cardiac catheterization, 278 +93 cGy and 244 +138 cGy respectively (pZ0.699). Conclusion: Patients with significant CAD abnormalities identified on cardiac catheterization following left-side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, our finding contradicts what is documented in three studies that have found three different mechanisms through which obesity promotes metastasis [ 28 - 30 ]. Moreover, in another study that compared the median overall survival (MOS) with BMI, they concluded that women with a normal BMI had a MOS of 54 months, whereas, in women with an overweight BMI, this number decreased to 28 months [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our finding contradicts what is documented in three studies that have found three different mechanisms through which obesity promotes metastasis [ 28 - 30 ]. Moreover, in another study that compared the median overall survival (MOS) with BMI, they concluded that women with a normal BMI had a MOS of 54 months, whereas, in women with an overweight BMI, this number decreased to 28 months [ 31 ].…”
Section: Discussionmentioning
confidence: 99%